Oviposition ecology of Aedes mosquitoes in relation to indoor-outdoor light intensity and dengue endemicity in Aceh Besar, Indonesia - ARSIH YULIANTI; ALIA RIZKI; SUWARNO SUWARNO; NASRUL ARAHMAN; BASRI A. GANI; HUSNURRIZAL HUSNURRIZAL; HARAPAN HARAPAN; MUDATSIR MUDATSIR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yulianti A, Rizki A, Suwarno, Arahman N, Gani BA, Husnurrizal, Harapan, Mudatsir. 2025. Oviposition ecology of Aedes mosquitoes in relation to indoor-outdoor light intensity and dengue endemicity in Aceh Besar, Indonesia. Biodiversitas 26: 5803-5813. Dengue fever continues to pose a major public health problem in tropical regions, with Aedes aegypti and Aedes albopictus as the main vectors. While the effects of temperature, humidity, and rainfall on mosquito ecology are well documented, the influence of light intensity on oviposition behavior across areas with different dengue endemicity levels remains less understood. This study aimed to assess the influence of indoor-outdoor light intensity and dengue endemicity on oviposition activity of Aedes mosquitoes in Aceh Besar District, Indonesia. A cross-sectional ecological survey was conducted in two sub-districts classified as high and low endemicity, with three villages randomly selected from each. In total, 240 ovitraps (120 indoor and 120 outdoor) were deployed over two five-day sampling periods, accompanied by concurrent light intensity measurements using a lux meter. Ovitrap positivity and egg density were analyzed using logistic regression and the Mann-Whitney U test. Of all traps, 62.92% were positive for Aedes eggs. No significant differences in Ovitrap Index (OI) or oviposition activity were observed between locations or endemicity levels (both had p>0.05). Indoor light intensity had a significant effect on oviposition activity: dimly lit households in high-endemicity areas recorded higher oviposition (1.67%, p: 0.01 and 3.33%, p: 0.02, respectively). Outdoor oviposition showed no significant variation by light intensity. These results indicate that low indoor lighting favors Aedes oviposition regardless of endemicity level. Improving household illumination may reduce suitable oviposition habitats and serve as a practical addition to existing vector control strategies.